Mathematical modelling of combined infrared and hot air drying of sliced sweet potato (Ipomoea batatas L.) - Onwude, Daniel Iroemeha Chikwendu (2018)
Combined infrared and hot-air drying method has been identified to be able to improve both energy efficiency and quality of dried agricultural crops. However, being a novel drying technique, studies on its application to the drying of industrial crops such as sweet potato are still limited. Particularly, the drying conditions, combination strategies and modelling studies are not properly investigated. This research investigated the potential of combined infrared and hot-air in drying of sweet potato (Ipomoea batatas L.) slices. The combined computer vision (CV) and laser-light backscattering imaging was adopted to monitor the shrinkage and quality attributes. The specific energy consumption (SEC), colour and microstructural changes of sweet potato (Ipomoea batatas L.) based on experimental set-up of different combined IR and HAD strategies (Simultaneous IR and HAD, two-stage HAD + IR, two-stage IR + HAD, intermittent IR and HAD) were investigated. Mathematical models based on Lambert’s equation of electromagnetics for single-phase and multiphase change during the combined IR and HAD of sweet potato were developed and evaluated, using finite element methods in both COMSOL and MATLAB software. The combined IR and HAD resulted in 69.34 – 85.59% reduction in the SEC of HAD. The specific energy consumption during simultaneous IR and HAD, two-stage HAD+IR, two-stage IR+HAD, and intermittent IR and HAD varied between 174.10- 310.93 MJ/kg, 95.80-177.48 MJ/kg, 56.30-68.36 MJ/kg, 99.61-149.18 MJ/kg, respectively. The intermittent IR and HAD was demonstrated to be the most suitable combination strategy based on the combined effect of total drying time, shrinkage, SEC and total colour change. The moisture and temperature distribution results of the single-phase model for simultaneous and intermittent IR and HAD of sweet potato agreed well with experimental drying data. The multiphase simulations results indicated that the model could adequately describe the underling drying mechanism of combined IR and HAD. The water and vapour fluxes due to gas diffusion and gas pressure resulted to increased drying efficiency of combined IR and HAD. The understanding of these phenomenon could be used to improve food quality and increase energy efficiency. The automation and optimization ability could also be increased.